1995
DOI: 10.1126/science.268.5211.700
|View full text |Cite
|
Sign up to set email alerts
|

Metal Nanotubule Membranes with Electrochemically Switchable Ion-Transport Selectivity

Abstract: Membranes containing cylindrical metal nanotubules that span the complete thickness of the membrane are described. The inside radius of the nanotubules can be varied at will; nanotubule radii as small as 0.8 nanometer are reported. These membranes show selective ion transport analogous to that observed in ion-exchange polymers. Ion permselectivity occurs because excess charge density can be present on the inner walls of the metal tubules. The membranes reject ions with the same sign as the excess charge and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
767
0
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 647 publications
(790 citation statements)
references
References 16 publications
17
767
0
6
Order By: Relevance
“…It can also be viewed as a universal ion exchange membrane, 30 where similar membrane potential modulation has been observed. The experimental results on quasi-statically converting the transmembrane ion gradients into potential validate the voltage regulated selectivity mechanism.…”
mentioning
confidence: 88%
“…It can also be viewed as a universal ion exchange membrane, 30 where similar membrane potential modulation has been observed. The experimental results on quasi-statically converting the transmembrane ion gradients into potential validate the voltage regulated selectivity mechanism.…”
mentioning
confidence: 88%
“…Perhaps most importantly, we have demonstrated a desirable and readily attainable feature of specifically tailoring transport through a suitable choice of encapsulating ligand chemically absorbed to the NP surface. In this regard, we are able to achieve a desired functionality in a manner similar to, but distinctly different from, those using self-assembled monolayers (SAMs) [35][36][37][38][39][40][41] , b a (1), under the assumption of a fixed membrane charge density, |X|. Deviations to the model are most prevalent at low electrolyte concentration, resulting from the fact that |X| is not a constant, but depends on the electrolyte concentration as shown in the inset.…”
Section: Article Nature Communications | Doi: 101038/ncomms6847mentioning
confidence: 94%
“…Here by utilizing particles encoded a priori with the desired functionality, we are able to bypass the requirement of a favourable surface chemistry in order to bind the molecules to the surface of the porous substrate itself, or any additional steps coating the substrate with a metal such as gold [38][39][40][41] . Owing to the flexibility by which ligated NPs can be synthesized, including both the core materials themselves and the encapsulating ligands 43,44 , we believe the approach outlined here can be generalized to a similar set of functionalities as their SAM counterparts for different core materials.…”
Section: Article Nature Communications | Doi: 101038/ncomms6847mentioning
confidence: 99%
“…If the pore walls are made of conductive material, the wall charge can be altered by applying a prescribed potential to the membrane. In this way, the membrane selectivity characteristics can be externally varied and controlled [5,6]. A comprehensive review of charged membranes applications can be found in [7].…”
Section: Introductionmentioning
confidence: 99%
“…The considered electrolyte concentrations were 1 mol/m 3 and lower except the work [24] (the pressure-driven flow was not considered there). However, typical nanofiltration membranes have the pore diameter of a few nanometers and the aspect ratio of order 100-1000, while the electrolyte concentration can be as high as 1000 mol/m 3 [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%